Analisa Perkembangan Counter Pulsa Hand Phone Di Kabupaten Lumajang Menggunakan Perhitungan Break Even Point (BEP) dan Analisis Regresi Linear Sederhana - Amalia, Riezky; Siswanto; Mustofa, Ahmad; Setyawan, Bimo (Jurnal Absis: Jurnal Pendidikan Matematika dan Matematika, 2024)
This study aims to analyze the development of sales turnover and profits of mobile phone credit counters in Lumajang Regency using a combination of Break Even Point (BEP) calculation and simple linear regression methods over the period 2018 - 2022. Through direct surveys with mobile phone counter owners, it was found that they face difficulties in monitoring the development of their sales turnover and profits. The results show that to reach the break-even point, the average minimum transaction per year is 20 transactions with an additional sale of at least 2 other product units. The break-even point for mobile phone credit sales is recorded at a minimum turnover of IDR 69,342,600, while other products reach IDR 426,116,200. The minimum break-even cost for mobile phone credit sales is IDR 29,144. Additionally, this study reveals that profits have decreased by an average of IDR 3,600 per year. These findings provide important insights for business owners to understand the dynamics of their businesses and strategies for improving profitability.